2019
DOI: 10.1016/j.ejpoleco.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Does corruption hinder investment? Evidence from Russian regions

Abstract: This paper investigates the causal relationship between corruption and fixed capital investment in Russian regions. The panel data on corruption allow to control for unobserved heterogeneity with fixed effects estimation. We address the problem of endogeneity by introducing novel instrumental variables for corruption: the presence of free press and violations of journalists' rights. Our main result is the strong negative effect of corruption on aggregate investment in fixed capital. Disaggregating investment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 94 publications
1
35
0
3
Order By: Relevance
“…The overall investment performance in the region is "offset" by its fragmentarity, lack of core development conditions (Zakharov, 2019). Moreover, it shall be highlighted that the current system of investment support in the republic implies limited implementation of the following strategically important functions:…”
Section: Resultsmentioning
confidence: 99%
“…The overall investment performance in the region is "offset" by its fragmentarity, lack of core development conditions (Zakharov, 2019). Moreover, it shall be highlighted that the current system of investment support in the republic implies limited implementation of the following strategically important functions:…”
Section: Resultsmentioning
confidence: 99%
“…Several scholars have demonstrated that corruption has significant effects on the entrepreneurial ecosystem and economic development of a country (Moiseev and Goncharova 2019;Zakharov 2019;Bardhan 1997;Mauro 1995). More recently, scholars have underlined that people's perceptions about corruption and the efficacy of governmental efforts to fight corruption are important elements of their cognitive-cultural dimension and have been greatly underestimated as influences of peoples' entrepreneurial intentions (Aparicio et al 2016;Neneh 2014;North 1991;Stenholm et al 2013).…”
Section: Corruption and Entrepreneurial Intentionsmentioning
confidence: 99%
“…In the study on regional level analysis of the Russia, (Mariev, Drapkin, Chukavina, Heiko, 2016) stated that the gross domestic product of the investor's country, the gross domestic product per capita in the recipient region, the distance from the investor to Moscow, the openness of the region, the economic situation in the region, the innovative capacity of the region, and the foreign direct investment of the previous period significantly determine the FDI in the Russia but the distance from the recipient region to Moscow matters in the western part of Russia only while does not in the eastern part (remote regions). Besides, N. Zakharov found the common negative relationship between the corruption measured by the bribery taking, the freedom of journalism, and the investments, in spite of the different influence depending on company types: bigger for private companies while smaller for public companies (Zakharov, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%